Development of 408MHz V-shape Dipole-based Antenna for Solar Observation - Anwar, Radial; Tariqul Islam, Mohammad; Misran, Norbahiah; Zavvari, Azam; Yatim, Baharudin; Fairos Asillam, Mhd (International Journal of Engineering and Technology, 2019)
Solar is one of the most observed object in a radio astronomy, as it is highly affects the space weather. In this paper, a new 408 MHz dipole-based antenna for solar radio telescope system is presented. High gain up to 11.30 dBi with beamwidth size of about 58Â° has been achieved by optimizing the structure of parasitic elements on the antenna. Measurement result shows a good agreement with simulation, with error rate on frequency peak down to 0.98%. The proposed antenna has been utilized in several solar observation and the results are also presented in this paper.Â
Keywords: V-Shape; Dipole-based Antenna; Solar Observation.